Embryonal Rhabdomyosarcoma of the Testis - Rahman, Ayesha; Alam, SM Syeed Ul; Sultana, Salma (Journal of Surgical Sciences, 2020)
Rhabdomyosarcoma (RMS), arising from mesenchymal cells, is the most common soft tissue tumour in children and accounts for up to half of all sarcomas. We present a case of a 15 year old male presented with gradually increasing right sided scrotal swelling for last one year. The patient was later diagnosed as right testicular malignancy with metastasis in abdominal lymph nodes and lungs. Inguinal orchidectomy was performed and final histopathological diagnosis was embryonal rhabdomyosarcoma of right testis. Journal of Surgical Sciences (2019) Vol. 23(2): 98-99